Legal Protection for Land Rights Holders Against Mapping (Plotting) Errors in Electronic Land Certificates - Damayanti, Retno; Kurniati, Nia; Rubiati, Betty (Al-Risalah, 2025)
The digital transformation of Indonesia’s land administration through electronic land certificates aims to improve transparency and legal certainty. However, spatial plotting errors remain a critical obstacle that undermines the certificates’ validity and public trust. This study examines the legal validity of electronic certificates containing plotting errors and the forms of legal protection available to rights holders within the framework of digital land governance. Using a normative juridical method with statutory, conceptual, and case approaches, the research reveals that such errors weaken the material legal force of certificates, as they no longer reflect actual land boundaries. The study’s novelty lies in its integration of digital accountability and administrative law principles, highlighting the state’s responsibility to ensure data accuracy and equitable protection in electronic land registration.